Adaptação estratégica organizacional no setor elétrico brasileiro: estudo de caso em Furnas Centrais Elétricas - Cota, Paulo Roberto dos Santos (2006)
The following study describes and analyzes how the process of strategic adaptation of FURNAS CENTRAIS ELÉTRICAS S. A. was developed between 1975 and 2004; with the purpose of determine which were the strategic changes and how they were developed. This research is based on the study of the political scenery, in the level of historical perception of strategic changes, by qualitative research and non-structured interviews using the Pettigrew (1987) methodology, with the purpose of evaluating the internal and external surroundings and understanding the strategic changes implemented. The surroundings contexts were presented in three periods:the first one (1975 to 1984) boards the growth of electrical energy state companies; the second one (1985 to 1994) contains the economical crises scenery; and the third one (1995 to 2004) shows the rebirth of the Brazilian electrical sector. In conclusion, the company adopted strategic proceedings depending on the characteristics of each analyzed period, and searched always the adaptation of the company to the new surroundings